High-strength dual-network self-healing hydrogel and composition, preparation method and application thereof

By constructing a dual network structure of chitosan, hyaluronic acid and polyvinyl alcohol, using dynamic Schiff base bonds and dynamic borate ester bonds, the strength and self-healing performance of self-healing hydrogels in the prior art are solved. The contradiction between the two achieves both high strength and excellent self-healing performance.

CN119424722APending Publication Date: 2025-02-14CHONGQING UNIVERSITY OF SCIENCE AND TECHNOLOGY

Patent Information

Application Number
CN202411405061.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

While improving mechanical strength, existing self-healing hydrogels often have contradictions between self-healing performance and strength, making it difficult to have both high strength and excellent self-healing performance.

Method used

Using chitosan, hyaluronic acid and polyvinyl alcohol as raw materials, through modification treatment and introduction of sodium tetraborate, a dual network structure of dynamic Schiff base bond and dynamic borate bond is constructed to form a high-intensity dual network self-healing Hydrogel.

Benefits of technology

It achieves high strength and excellent self-healing performance, with an elastic modulus of 148.60KPa, and can completely heal within 3 seconds. It also has good rebound performance, injectability, swelling performance, shape memory and ionic conductivity .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119424722A_ABST
    Figure CN119424722A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of medical materials, and particularly relates to high-strength dual-network self-healing hydrogel as well as a composition, a preparation method and application thereof. The composition for preparing the high-strength dual-network self-healing hydrogel comprises a composition A for constructing a first network system of the hydrogel and a composition B for constructing a second network system of the hydrogel, wherein the composition A comprises modified chitosan and modified hyaluronic acid, and the composition B comprises polyvinyl alcohol and sodium tetraborate; the volume ratio of the polyvinyl alcohol to the modified chitosan to the modified hyaluronic acid is (5-7): (5-7): 1; the concentration of the modified chitosan is 2-4 wt%, the concentration of the modified hyaluronic acid is 8-12 wt%, and the concentration of the polyvinyl alcohol is 18-22 wt%. The high-strength dual-network self-healing hydrogel prepared on the basis of the composition has relatively high mechanical performance and excellent self-healing performance, and also has excellent resilience performance, swelling performance, shape memory and ionic conduction behavior.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of medical materials, and in particular relates to a high-strength double-network self-healing hydrogel and a composition, a preparation method and an application thereof. Background Art

[0002] Hydrogel is a polymer material with a three-dimensional network structure that can absorb and retain a large amount of water without dissolving, and has good flexibility and biocompatibility. On this basis, self-healing hydrogels can self-repair their structure and function after being damaged by external damage through dynamic reversible chemical bonds or physical interactions. Therefore, while retaining the water absorption and water retention properties of traditional hydrogels, self-healing hydrogels also have excellent self-repairing properties, biocompatibility, stimulus responsiveness, and longer service life and reuse rate.

[0003] In addition to the self-healing properties, the ideal hydrogel for wound dressing should also have the characteristics of high strength and good toughness. However, traditional self-healing hydrogels are generally soft and fragile, and the self-healing performance and high strength are often contradictory. Most hydrogels with appropriate self-healing behavior show low strength, which seriously limits their application in the field of wound dressings. At present, technicians in this field have conducted a lot of research on the strength increase of self-healing hydrogels, mainly including nanocomposite reinforcement, double network and hydrophobic association hydrogel reinforcement. Among them, the research on improving the mechanical strength of self-healing hydrogels through double network systems is the most. The double network hydrogel consists of two different networks. The first layer is a high-density cross-linked network as a rigid skeleton structure, and the second layer is a sparsely cross-linked network filled in the first layer of the network. When used as a wound dressing, the high-strength double network self-healing hydrogel can reduce the number of dressing changes, achieve wound visualization, and protect granulation tissue, while having the advantages of repair and skin regeneration.

[0004] In the prior art, the invention patent with publication number CN116751432A discloses an antibacterial self-healing composite double network hydrogel, which is made of the following raw materials in mass percentage: 15% acrylic acid, 7.5% polyvinyl alcohol, 1.50-2.23% cellulose nanofibers, 0.25% borax, 0.37-0.74% tannic acid, 0.06% crosslinking agent, 0.22% initiator, and the balance is water. This patent is to prepare a nano-composite double network hydrogel with antibacterial, adhesive and self-healing properties by embedding tannic acid and cellulose nanofibers into the borax-polyvinyl alcohol / polyacrylic acid hydrogel network and adopting a chemical and physical double crosslinking network construction method. The mechanical properties of this composite double network hydrogel are not very ideal.

[0005] Although some progress has been made in the research of double network self-healing hydrogels, there are still many technical challenges due to their complex multi-level structure and multi-factor interaction mechanism. Therefore, the development of a double network hydrogel with both high mechanical properties and excellent self-healing properties is of great significance for the development of new dressings. Summary of the invention

[0006] In order to overcome the defects of the prior art, the present invention has carried out in-depth research on double network hydrogels, and proposed a high-strength double network self-healing hydrogel and its composition, preparation method and application. The present invention uses chitosan, hyaluronic acid and polyvinyl alcohol as raw materials, modifies chitosan and hyaluronic acid, and introduces sodium tetraborate to construct a high-strength double network self-healing hydrogel with dynamic Schiff base bonds formed by chitosan / hyaluronic acid and dynamic borate ester bonds formed by polyvinyl alcohol and sodium tetraborate after cyclic freezing-thawing. The high-strength double network self-healing hydrogel has both excellent self-healing properties and high mechanical properties.

[0007] One of the purposes of the present invention is to provide a composition for preparing high-strength double-network self-healing hydrogel.

[0008] To achieve the above object, the present invention adopts the following technical solutions:

[0009] A composition for preparing a high-strength double-network self-healing hydrogel, the composition comprising composition A for constructing a first network system of a hydrogel and composition B for constructing a second network system of a hydrogel; the composition A comprises modified chitosan and modified hyaluronic acid, the composition B comprises polyvinyl alcohol and sodium tetraborate; the volume ratio of the polyvinyl alcohol, the modified chitosan and the modified hyaluronic acid is 5-7:5-7:1; the concentration of the modified chitosan is 2wt%-4wt%, the concentration of the aldehyde-modified hyaluronic acid is 8wt%-12wt%, and the concentration of the polyvinyl alcohol is 18wt%-22wt%.

[0010] Furthermore, the amino group on the modified chitosan is coupled with acrylic acid; and the modified hyaluronic acid is aldehyde-modified hyaluronic acid.

[0011] Furthermore, the amino group of the modified chitosan and the aldehyde group of the modified hyaluronic acid form a dynamic Schiff base bond to form a first network; the sodium tetraborate and the polyvinyl alcohol form a dynamic borate ester bond to form a second network.

[0012] Furthermore, the concentration of the sodium tetraborate is 0.5wt% to 2wt%.

[0013] Preferably, the concentration of the modified chitosan is 3wt%, the concentration of the aldehyde-modified hyaluronic acid is 10wt%, the concentration of the polyvinyl alcohol is 20wt%, and the concentration of the sodium tetraborate is 1wt%.

[0014] Preferably, the volume ratio of the polyvinyl alcohol, modified chitosan and aldehyde-modified hyaluronic acid is 6:6:1.

[0015] The second object of the present invention is to provide a method for preparing a high-strength double-network self-healing hydrogel.

[0016] To achieve the above object, the present invention adopts the following technical solutions:

[0017] The preparation method of high-strength double-network self-healing hydrogel comprises the following steps:

[0018] (1) dissolving acrylic acid and adding chitosan, coupling the amino groups on chitosan with acrylic acid through Michael reaction to obtain modified chitosan;

[0019] (2) mixing hyaluronic acid with sodium periodate to prepare aldehyde-modified hyaluronic acid through an oxidation reaction;

[0020] (3) mixing the modified chitosan obtained in step (1), the aldehyde-modified hyaluronic acid obtained in step (2) and polyvinyl alcohol, and rapidly stirring to form a gel; and soaking in sodium tetraborate after cyclic freezing-thawing to obtain the high-strength double-network self-healing hydrogel.

[0021] Furthermore, in step (1), the reaction conditions of the Michael reaction are: heating and stirring at 90°C to 100°C for 2.5 to 4 days.

[0022] Preferably, the temperature of the heating and stirring reaction is 95° C. and the time is 3 days.

[0023] Furthermore, step (1) specifically includes the following: dissolving acrylic acid with deionized water, adding chitosan, heating and stirring in a 95° C. water bath for 3 days; adjusting the pH of the solution to 10-12, dialyzing, and freeze-drying to obtain modified chitosan.

[0024] Preferably, the pH adjuster is 1 mol / L NaOH.

[0025] Preferably, in step (1), dialysis is performed for three days using an 8000 MD dialysis bag.

[0026] Furthermore, in step (2), the oxidation reaction conditions are: 20°C to 30°C in the dark for 7h to 10h.

[0027] Preferably, in step (2), the oxidation reaction conditions are: 25° C. in the dark for 8 hours.

[0028] Furthermore, step (2) comprises: adding sodium periodate aqueous solution dropwise into a hyaluronic acid aqueous solution with a concentration of 1 wt% under light-proof conditions; continuing the reaction under light-proof conditions at 25° C. for 8 h; adding ethylene glycol after the reaction is completed and continuing stirring for 1 h; dialyzing and freeze-drying to obtain aldehyde-modified hyaluronic acid.

[0029] Preferably, in step (2), a 3500 MD dialysis bag is used for dialysis for three days.

[0030] Furthermore, the molar ratio of the sodium periodate to the hyaluronic acid repeating unit is 1.2:1.

[0031] Furthermore, in step (3), the number of freeze-thaw cycles is 2 times, the single freezing time is 2.5 h to 3.5 h, and the thawing time is 1.5 h to 2.5 h.

[0032] Preferably, the single freezing time is 3 hours and the thawing time is 2 hours.

[0033] Furthermore, in step (3), the sodium tetraborate soaking time is 25 min to 60 min, preferably 30 min.

[0034] The third object of the present invention is to provide a high-strength double-network self-healing hydrogel prepared by the aforementioned method.

[0035] A fourth object of the present invention is to provide a preparation composition having an antibacterial effect.

[0036] To achieve the above object, the present invention adopts the following technical solutions:

[0037] A preparation composition with antibacterial effect, the preparation composition comprises the above-mentioned composition and an antibacterial drug, the antibacterial drug comprises doxycycline hydrochloride, and the carrier of the antibacterial drug is polyvinyl alcohol.

[0038] A fifth object of the present invention is to provide a use of the aforementioned composition, the aforementioned high-strength double-network self-healing hydrogel and / or the aforementioned preparation composition in the preparation of a high-strength self-healing wound dressing.

[0039] Furthermore, the aforementioned composition, the aforementioned high-strength double-network self-healing hydrogel and / or the aforementioned preparation composition are used in the preparation of wound dressings with high mechanical strength, self-healing properties, resilience, injectability, swelling properties, shape memory and / or ion conductive behavior.

[0040] Furthermore, the aforementioned preparation composition is used in the preparation of a high-strength self-healing antibacterial wound dressing.

[0041] The beneficial effects of the present invention are:

[0042] 1. The present invention adopts chitosan with excellent antibacterial performance and biocompatibility, hyaluronic acid with good water absorption and water locking effect, and polyvinyl alcohol with high mechanical strength. Three raw materials are used to construct a double network self-healing hydrogel with chitosan / hyaluronic acid dynamic Schiff base and polyvinyl alcohol / sodium tetraborate borate bond based on cyclic freezing-thawing method, wherein the first network is a flexible gel network generated by the Schiff base reaction of chitosan and hyaluronic acid, and PVA forms a rigid and hard second network by cyclic freezing-thawing. The present invention adopts a simple cyclic freezing method to introduce the second network system of polyvinyl alcohol / sodium tetraborate system in the chitosan / hyaluronic acid single network self-healing hydrogel system. While improving the mechanical properties, the self-hydrogen bonds of polyvinyl alcohol and the hydrogen bonds and dynamic borate bonds formed between molecules also improve the self-healing performance, which provides new ideas and research methods for the development of high-strength new dressings.

[0043] 2. The present invention explores the effects of raw material concentration, raw material ratio, freeze-thaw cycle times and cross-linking agent sodium tetraborate addition method on mechanical properties, morphology, self-healing properties, shape memory and antibacterial behavior in single and double network structures, and obtains the best preparation process of high-strength double network self-healing hydrogel. The preparation method is simple and environmentally friendly, and does not introduce other organic cross-linking systems.

[0044] 3. The high-strength double-network self-healing hydrogel provided by the present invention has both excellent self-healing properties and high mechanical properties, and its elastic modulus can reach 148.60KPa, and it can self-heal within 3s; at the same time, the self-healing hydrogel has a uniform and dense three-dimensional porous structure, excellent resilience, injectability, swelling performance, shape memory, ion conductivity, etc. The present invention provides a new idea for the preparation of hydrogels with both high strength and self-healing properties, and is expected to provide a reference for the development of new wound dressings.

[0045] 4. The high-strength double-network self-healing hydrogel provided by the present invention can be further loaded with antibacterial drugs such as doxycycline hydrochloride. The obtained drug-loaded hydrogel has excellent drug release behavior and antibacterial properties. It not only has a good antibacterial effect, but also has a long and slow drug release cycle, which provides a guarantee for the recycling of wound dressings. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] Figure 1 It is the CEC modification reaction formula;

[0047] Figure 2 is the OHA modification reaction formula;

[0048] Figure 3 It is the reaction formula of CEC / OHA single network self-healing hydrogel;

[0049] Figure 4is a self-healing hydrogel formation diagram, where: Figure 4 -A is a graph of chitosan solution, Figure 4 -B is a picture of hyaluronic acid solution, Figure 4 -C is a diagram of tilted chitosan / hyaluronic acid self-healing hydrogel, Figure 4 -D is a diagram of inverted chitosan / hyaluronic acid self-healing hydrogel;

[0050] Figure 5 It is the CEC modified H NMR spectrum;

[0051] Figure 6 This is the H NMR spectrum of OHA aldehyde modification;

[0052] Figure 7 The stress-strain and elastic modulus diagrams of single network hydrogels with different CEC / OHA ratios, where Figure 7 -A is the stress-strain diagram of single network hydrogels with different CEC / OHA ratios, Figure 7 -B is the elastic modulus diagram of single network hydrogels with different CEC / OHA ratios;

[0053] Figure 8 The stress-strain and elastic modulus diagrams of double network hydrogels under different sodium tetraborate addition methods; Figure 8 -A is the stress-strain diagram of the double network hydrogel under different sodium tetraborate addition methods, Figure 8 -B is the elastic modulus diagram of the double network hydrogel under different sodium tetraborate addition methods;

[0054] Fig. 9 The stress-strain and elastic modulus diagrams of the double network hydrogel under different freezing-thawing cycles, where: Fig. 9 -A is the stress-strain diagram of the double network hydrogel under different freezing-thawing times, Fig. 9 -B is the elastic modulus diagram of the double network hydrogel under different freezing-thawing times;

[0055] Fig.10 The stress-strain and elastic modulus diagram of the double network hydrogel at different PVA addition amounts during the second cycle, where: Fig.10 -A is the stress-strain diagram of the double network hydrogel under different PVA addition amounts, Fig.10 -B is the elastic modulus diagram of the double network hydrogel at different PVA addition amounts;

[0056] Fig.11 This is the SEM image of the sample under 6:1 single network, where: Fig.11 -A is a 500-fold magnified SEM image of a 6:1 single network sample. Fig.11 -B is a SEM image of a 6:1 single network sample magnified 1000 times;

[0057] Fig.12 This is the SEM image of the sample under 6:6:1 dual network / 0 cycles, where: Fig.12 -A is a 500-fold magnified SEM image of a 6:6:1 dual network / 0 cycle sample. Fig.12 -B is a SEM image of a 6:6:1 dual network / 0 cycle sample magnified 1000 times;

[0058] Fig.13 This is the SEM image of the sample under 6:6:1 double network / 1 cycle, where: Fig.13 -A is a 500-fold magnified SEM image of a 6:6:1 dual network / 1 cycle sample. Fig.13 -B is a SEM image of a 6:6:1 dual network / 1 cycle sample magnified 1000 times;

[0059] Fig.14 This is the SEM image of the sample under 6:6:1 double network / 2 cycles, where: Fig.14 -A is a 500-fold magnified SEM image of a 6:6:1 dual network / 2-cycle sample. Fig.14 -B is a 1000-fold magnified SEM image of a 6:6:1 dual network / 2-cycle sample;

[0060] Fig.15 This is the SEM image of the sample under 6:6:1 double network / 3 cycles, where: Fig.15 -A is a 500-fold magnified SEM image of a 6:6:1 dual network / 3-cycle sample. Fig.15 -B is a SEM image of a 6:6:1 dual network / 3 cycles sample magnified 1000 times;

[0061] Fig.16 It is a statistical chart of the pore sizes of different samples;

[0062] Fig.17 Schematic diagram of hydrogel self-healing;

[0063] Fig.18 is the self-healing process diagram, where Fig.18 -A is a diagram of the self-healing process of a single network hydrogel at the microscopic level. Fig.18 -B is a diagram of the self-healing process of a single network hydrogel under macroscopic conditions. Fig.18 -C is a microscopic diagram of the self-healing process of the double network hydrogel. Fig.18 -D is the self-healing process diagram of the double network hydrogel under macroscopic conditions;

[0064] Fig.19 The stress-strain curve and elastic modulus diagram of single network / double network before and after self-healing, where: Fig.19-A is the stress-strain curve of 6:1 single network and 6:6:1 double network / 2 cycles before and after self-healing, Fig.19 -B is the elastic modulus diagram of 6:1 single network and 6:6:1 double network / 2 cycles before and after self-healing;

[0065] Fig. 20 This is a graph showing the test results of the hydrogel's self-healing and injectable properties;

[0066] Fig.21 This is a diagram of the rebound process under mechanical instruments;

[0067] Fig. 22 The results of stretching the hydrogel under the same scale are shown;

[0068] Fig.23 It is the swelling performance curve;

[0069] Fig.24 is the shape memory behavior process diagram,

[0070] Fig.25 The statistical diagram of hydrogel ion conductivity under different preparation conditions;

[0071] Fig.26 This is a diagram of the ion conduction process. From left to right, the light is on when the connection is not cut off, the light is off when the connection is cut off, and the light is on when the connection is reconnected.

[0072] Fig. 27 is the cumulative release curve of drug loading;

[0073] Fig.28 is the antibacterial behavior and inhibition zone diameter diagram, among which, Fig.28 -A is the antibacterial behavior and inhibition zone diameter of the 6:1 single network sample. Fig.28 -B is the antibacterial behavior and inhibition zone diameter of the 6:6:1 double network / 0 cycle sample. Fig.28 -C is the antibacterial behavior and inhibition zone diameter of the 3:6:1 double network / 2 cycles sample. Fig.28 -D is the antibacterial behavior and inhibition zone diameter of the sample with 6:6:1 double network / 2 cycles (PVA 20wt%), Fig.28 -E is the antibacterial behavior and inhibition zone diameter of the sample with 6:6:1 double network / 2 cycles (PVA 15wt%);

[0074] Fig.29 It is a statistical chart of the diameter of the inhibition zone. DETAILED DESCRIPTION

[0075] The technical solution of the present invention will be further described clearly and completely in conjunction with specific embodiments below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Therefore, based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work belong to the protection scope of the present invention.

[0076] In the present invention, chitosan (CEC) is a positively charged amino-rich polysaccharide, which plays an important role in wound cleaning, disinfection, antibacterial and anti-inflammatory protection of wound surface, etc. Due to its similarity with the natural extracellular matrix, chitosan has good biocompatibility, biodegradability and hydrophilicity. At the same time, chitosan also has excellent swelling characteristics, excellent antibacterial properties and high sensitivity, and has a natural advantage for preparing self-healing hydrogels. Chitosan can also be used as a hemostatic agent to coagulate blood at nerve endings and relieve pain, so it is widely used in the field of wound dressings.

[0077] In the present invention, hyaluronic acid (HA) is a non-sulfated glycosaminoglycan found in the extracellular matrix of vertebrate tissues, has good hydrophilicity, fluidity and water absorption, and is a good choice as a wound dressing material.

[0078] In the present invention, polyvinyl alcohol (PVA) is one of the most important hydrophilic polymers in the field of wound dressings, and has ideal properties such as good biocompatibility, non-immunogenicity and multiple physical properties. The hydrogen bonded crystalline domains of the polyvinyl alcohol network make the hydrogel have toughness, fatigue resistance, rapid recovery and self-healing properties. At the same time, the properties of polyvinyl alcohol hydrogel similar to human skin make it have mechanical properties similar to natural skin, and it has great application prospects in the field of wound dressings.

[0079] In the embodiment of the present invention, chitosan, hyaluronic acid and polyvinyl alcohol are used as main raw materials to construct a high-strength double-network self-healing hydrogel. The cross-linking mechanism of the self-healing hydrogel is that the amino group of chitosan and the aldehyde group of hyaluronic acid form a dynamic Schiff base bond, and polyvinyl alcohol and sodium tetraborate form a dynamic borate ester bond.

[0080] In the embodiments of the present invention, the main experimental instruments are shown in Table 1.

[0081] Table 1. List of experimental instruments

[0082] Device Name Device Model use Ultrasonic Cleaner SB-5200DTDN dispersion UV-Vis Spectrophotometer UV755B analyze Multi-head magnetic stirrer HJ-4A Stirring Electric constant temperature incubator XMA-600 nourish Scanning electron microscopy DX-7000 analyze Bacterial incubator Thermo nourish Constant temperature heating magnetic stirrer DF-101S heating Mechanical testing machine Sansi Taijie Measurement

[0083] In the examples of the present invention, the main experimental raw materials are shown in Table 2.

[0084] Table 2. List of experimental raw materials

[0085] Test materials Molecular formula Relative molecular weight purity Chitosan <![CDATA[C 6n H 11n NO 4n ]]> — — Hyaluronic acid <![CDATA[(C 14 H 21 NO 11 ) n ]]> 403.31 — Polyvinyl alcohol 1788 low viscosity type <![CDATA[[-CH 2 CHOH-] n ]]> 44.05 — Sodium Tetraborate <![CDATA[Na 2 B 4 O 7 ·10H 2 O]]> 381.37 Analytical grade Sodium periodate <![CDATA[NaIO 4 ]]> 346.34 Analytical grade Ethylene glycol <![CDATA[C 2 H 6 O 2 ]]> 62.07 Analytical grade acrylic acid <![CDATA[C 3 H 4 O 2 ]]> 72.06 Analytical grade Sodium hydroxide NaOH 40 Analytical grade Rhodamine B <![CDATA[C 28 H 31 ClN 2 Oh 3 ]]> 479.01 Analytical grade Doxycycline hydrochloride <![CDATA[C 22 H 25 ClN 2 Oh 8 ]]> 480.90 ACS-level hydrochloric acid HCl 36 Analytical grade

[0086] In the embodiment of the present invention, polyvinyl alcohol with a concentration of 15 wt % is prepared by weighing 15 g of polyvinyl alcohol into a 150 mL beaker, adding 85 mL of deionized water measured by a measuring cylinder, and stirring with a magnetic stirrer until the solution is uniform.

[0087] In the embodiment of the present invention, polyvinyl alcohol with a concentration of 20 wt % is prepared by weighing 20 g of polyvinyl alcohol into a 150 mL beaker, adding 80 mL of deionized water measured by a measuring cylinder, and stirring with a magnetic stirrer until the solution is uniform.

[0088] In the embodiment of the present invention, sodium tetraborate with a concentration of 1 wt% is prepared as follows: 1 g of polyvinyl alcohol is weighed and placed in a 150 mL beaker, 99 mL of deionized water is added, and the solution is stirred with a magnetic stirrer until the solution is uniform.

[0089] In the embodiment of the present invention, the preparation of NaOH with pH=11 is as follows: 0.001 g of NaOH is weighed and dissolved in a 100 mL volumetric flask, and secondary water is added to dilute the concentration, the pH is adjusted to 11, and finally the volume is made up to 100 mL and shaken for use.

[0090] In the embodiment of the present invention, the preparation of HCl with pH=4 is as follows: 0.001 g of HCl is weighed and dissolved in a 100 mL volumetric flask, and secondary water is added to dilute the concentration, the pH is adjusted to 4, and finally the volume is made up to 100 mL and shaken for use.

[0091] In the embodiment of the present invention, the preparation of hydroxylamine hydrochloride-methyl orange solution is as follows: 0.025g of methyl orange powder is weighed into a beaker, 50mL of deionized water is added, and the methyl orange aqueous solution with a concentration of 0.05% is dissolved and set aside; 4.34g of hydroxylamine hydrochloride is accurately weighed, 200mL of deionized water is added into a beaker to fully dissolve, a 250mL volumetric flask is taken, the solution in the beaker is poured into the volumetric flask, 2.5mL of 0.05% methyl orange aqueous solution is added, and the volume is fixed to the scale line, and shaken well.

[0092] Example 1

[0093] 1. Preparation of Chitosan Modification

[0094] Add 1.46 mL of acrylic acid to 50 mL of deionized water, then add 1 g of chitosan, heat and stir in a 95°C water bath for 3 days, adjust the pH to 10-12 with 1 mol / L NaOH, dialyze with an 8000 MD dialysis bag for three days, and freeze-dry to obtain a modified CEC sample. The modified chemical reaction formula is as follows: Figure 1 shown.

[0095] 2. Preparation of hyaluronic acid aldehyde modification

[0096] Dissolve 2g HA in 200mL deionized water, stir and fully dissolve at 25°C to obtain a 1% w / v hyaluronic acid aqueous solution. At the same time, dissolve 1.27g sodium periodate in 20mL water (the molar ratio of sodium periodate to HA repeating unit is 1.2:1), then add the sodium periodate aqueous solution drop by drop into the HA aqueous solution, continue to react in a 25°C water bath in the dark for 8h, then add 1mL ethylene glycol, continue to stir for 1h, dialyze with a 3500MD dialysis bag for three days, and freeze-dry to obtain the sample aldehyde-modified hyaluronic acid (OHA), the modified chemical reaction formula is as follows: Figure 2 shown.

[0097] 3. Preparation of Single Network Self-healing Hydrogel

[0098] This experiment used 3wt% CEC, and the CEC aqueous solution was transparent and viscous; the OHA concentration was 10wt%, and its aqueous solution was transparent water; the PVA concentrations were 15wt% and 20wt%, and their aqueous solutions were transparent and viscous; the sodium tetraborate concentration was 1wt%, and its aqueous solution was transparent water.

[0099] The single network hydrogel is formed by mixing and cross-linking CEC and OHA solutions. In the experimental process of the present invention, three single network self-healing hydrogels with a volume ratio of CEC to OHA of CEC:OHA = 2:1, 4:1 and 6:1 were prepared respectively. The experimental grouping is shown in Table 3. The specific reaction formula is as follows Figure 3 shown.

[0100] Table 3. Experimental groups of single network self-healing hydrogels

[0101] Sample No. sample 1 CEC / OHA=2:1 2 CEC / OHA=4:1 3 CEC / OHA=6:1

[0102] 4. Preparation of high-strength double-network self-healing hydrogel

[0103] CEC, OHA and PVA were mixed in proportion, stirred quickly to form gel, and then soaked or added with sodium tetraborate for 30 minutes after cyclic freezing-thawing to obtain double network self-healing hydrogel. In this experiment, hydrogels with 0, 1, 2, and 3 cycles of freezing-thawing were prepared according to the number of cycles of freezing-thawing. Each time, the hydrogels were frozen for 3 hours and then thawed for 2 hours. At the same time, the effects of the two different cross-linking methods of soaking in sodium tetraborate and adding sodium tetraborate and the different concentrations of PVA solution were explored. The specific groups are shown in Table 4.

[0104] Table 4. Double network hydrogel experimental grouping

[0105] Sample No. sample 4 PVA / CEC / OHA=6:6:1, 0 cycles (PVA 15wt%), borax soak 5 PVA / CEC / OHA=6:6:1, 1 cycle (PVA 15wt%), borax soak 6 PVA / CEC / OHA=6:6:1, 2 cycles (PVA 15wt%), borax soak 7 PVA / CEC / OHA=6:6:1, 3 cycles (PVA 15wt%), borax soak 8 PVA / CEC / OHA=6:6:1, 0 cycles (PVA 15wt%) with borax 9 PVA / CEC / OHA=6:6:1, 1 cycle (PVA 15wt%) with borax 10 PVA / CEC / OHA=6:6:1, 2 cycles (PVA 15wt%) with borax 11 PVA / CEC / OHA=6:6:1, 3 cycles (PVA 15wt%) with borax 12 PVA / CEC / OHA=3:6:1, 2 cycles (PVA 15wt%), borax soak 13 PVA / CEC / OHA=6:6:1, 2 cycles (PVA 20wt%), borax soak

[0106] Example 2. Analysis of self-healing hydrogel formation

[0107] The gelling properties of the product prepared in Example 1 were verified. Figure 4 As shown in the figure, after the chitosan solution and the hyaluronic acid solution were mixed and stirred, they stopped flowing after being tilted or inverted for a moment, indicating that a self-healing hydrogel was formed. The reaction mechanism was a dynamic reversible Schiff base reaction between the amino group on CEC and the aldehyde group on OHA. When PVA and sodium tetraborate were further introduced, the hydrogen bonds of PVA itself, the hydrogen bonds formed between molecules, and the dynamic borate ester bonds made the hydrogel cross-linked into a chemical-chemical double network hydrogel.

[0108] Example 3. Analysis of Aldehyde Modification of Chitosan and Hyaluronic Acid

[0109] In this example, the aldehyde groups of chitosan and OHA were successfully modified by nuclear magnetic resonance hydrogen spectrum, and the aldehyde group content and oxidation degree of OHA were calculated by hydrochloric acid-hydroxylamine titration method. The test method and results are as follows:

[0110] (1) Nuclear magnetic resonance hydrogen spectrum test

[0111] H NMR ( 1 H NMR) shows different absorption peaks and chemical shifts by testing the different chemical environments of hydrogen atoms in molecules. The size of the chemical shift can be used to qualitatively analyze whether the raw material modification is successful and the degree of modification. HA, OHA, CEC 0.8g is fully dissolved in 500μL deuterated water and injected into the NMR tube for NMR testing to verify whether it is successfully modified.

[0112] (2) OHA hydroformylation degree analysis

[0113] Using NaIO 4 The mechanism of HA oxidation is NaIO 4 It can break the chemical bond between two adjacent hydroxyl groups on the HA ring and oxidize them into two aldehyde groups. During the experiment, the hydrochloric acid-hydroxylamine method was used for quantitative detection. The test principle is that the amino group on hydrochloric acid-hydroxylamine is very active and can easily react with the aldehyde group on OHA, while releasing HCl. Therefore, the amount of HCl released can be titrated with NaOH to calculate the degree of hydroformylation. The specific test steps are: weigh about 0.1g OHA, add it to 25mL of hydrochloric acid hydroxylamine-methyl orange solution, stir magnetically to dissolve and place for 3h. Titrate it with 0.01mol / L sodium hydroxide solution to change it from red to yellow. The volume of sodium hydroxide consumed is recorded as V, and a blank control is made, and the volume is recorded as V 0 .

[0114] The calculation formula of aldehyde content is as follows:

[0115]

[0116] Among them, n NaOHis the molar concentration of NaOH used for titration, in mol / L.

[0117] The calculation formula of oxidation degree is as follows:

[0118]

[0119] Among them, n NaOH is the molar concentration of NaOH used for titration, in mol / L; W OHA is the mass of the sample measured, in g.

[0120] (3) Chitosan modification results

[0121] Chitosan is dissolved in acid, and the amino groups on chitosan are coupled with acrylic acid through Michael reaction to obtain water-soluble CEC. 1 H NMR Figure 5 As shown, the characteristic peak with a chemical shift of 1.96 ppm is the proton peak of acetamidomethyl (3-H), the characteristic peak with a chemical shift of 2.31 ppm is the proton peak of chitosan methylene (2-H), and the characteristic peak with a chemical shift of 4.97 ppm is the 1-H proton peak on the six-membered ring of chitosan, which reflects the proton peak on the chitosan molecular skeleton, showing the structural characteristics of chitosan and confirming that chitosan has been successfully grafted with acrylic acid. 1 The grafting degree was calculated to be 31% ± 0.03% by comparing the peak areas of “1” (3-H) and “2” (2-H) from H NMR spectrum.

[0122] (4) OHA aldehyde modification results

[0123] The aldehyde modification of OHA is obtained by oxidation reaction of hydroxyl (-OH) on the HA main chain. 1 HNMR Figure 6 As shown, compared with the NMR of HA, the oxidation of HA was confirmed. 1 A new C=O characteristic peak appeared at 4.8 ppm in H NMR, indicating that the aldehyde group modification was successful.

[0124] The aldehyde content and oxidation degree of OHA were further calculated by hydrochloric acid-hydroxylamine titration method. The results are shown in Table 5. When 13.5 mL of NaOH was consumed, the aldehyde content of HA was 0.067 mol and the oxidation degree was 27%.

[0125] Table 5. OHA aldehyde content and oxidation degree

[0126] sample NaOH consumption (mL) Aldehyde content (mol) Oxidation degree (%) OHA 13.5 0.067 27%

[0127] Example 4. Mechanical properties test

[0128] This example further analyzes the mechanical properties of a single network, the mechanical properties of a double network formed by different ways of adding borax, the mechanical properties of a double network formed by different freeze-thaw times, and the mechanical properties of a double network formed by adding different amounts of PVA. The mechanical property test method includes: the hydrogel compression test is carried out using a mechanical tester in a gel compression mode with a constant stress rate of 5N / min. At the moment of gel crushing, the instrument is immediately stopped, and the elastic modulus is calculated and the stress-strain curve is drawn based on the obtained data. In order to accurately evaluate the mechanical properties of hydrogels of different proportions, 5 parallel samples are set for each group of proportions, and cylindrical hydrogels (hydrogel: diameter 10mm, height 5mm) are used for measurement.

[0129] Stress calculation formula:

[0130]

[0131] The strain calculation formula is as follows:

[0132]

[0133] Among them, Load is the load value, unit is N; Position is the displacement, unit is mm.

[0134] The test results are as follows:

[0135] (1) Analysis of single network mechanical performance results

[0136] The stress-strain and elastic modulus diagram of a single network is shown in Figure 2. Figure 7 As shown. When CEC and OHA form single-network self-healing hydrogels of different concentrations, it can be seen that as the ratio of CEC to OHA increases, its mechanical properties also increase accordingly. When CEC:OHA=6:1, its stress can reach 29.65KPa and its elastic modulus can reach 34.50KPa, which is equivalent to 3 times that of CEC:OHA=2:1. The reason for this rule is that at the same ratio, the number of aldehyde groups on OHA is more than that of amino groups on CEC. When CEC:OHA=6:1, the amino groups on CEC can react almost completely with the aldehyde groups on OHA, so the formed hydrogel has the best mechanical properties. Based on this result, the subsequent experiments selected the ratio of CEC:OHA=6:1.

[0137] (2) Analysis of mechanical properties of double networks formed by different borax addition methods

[0138] Test results such as Figure 8 shown. Figure 8The stress-strain and elastic modulus diagram of the double network hydrogel prepared by different sodium tetraborate addition methods. It can be seen that the mechanical properties of the double network hydrogel soaked in sodium tetraborate under the same ratio are twice that of the double network hydrogel with sodium tetraborate. Among them, the elastic modulus of the double network hydrogel with borax added for 2 cycles is 68.13KPa, and that of the double network hydrogel with borax is 164.47KPa. This rule appears because sodium tetraborate itself is a cross-linking agent. When added to the double network system for cross-linking, it reacts with the PVA solution to quickly gel, resulting in uneven mixing between the components, which in turn makes its mechanical properties poor. Therefore, the method of soaking in sodium tetraborate is preferred for cross-linking.

[0139] (3) Analysis of mechanical properties of dual networks formed by different freezing-thawing times

[0140] Test results such as Fig. 9 shown. Fig. 9 The stress-strain and elastic modulus diagrams of double network hydrogels formed by different freeze-thaw cycles. The results show that the best mechanical properties are achieved when PVA:CEC:OHA=6:6:1 and freeze-thaw cycles are repeated twice, with stress up to 198.50KPa and elastic modulus up to 164.6KPa. The reason is that the crystallization of the PVA solution reaches the best effect when the freeze-thaw cycles are repeated twice. When the freeze-thaw cycles are repeated three times, the PVA solution will be over-crystallized, resulting in blockage of the three-dimensional pore structure and even collapse, thus affecting the mechanical properties. Among them, the mechanical properties of the double network hydrogel are much higher than those of the single network hydrogel at the same ratio, indicating that the introduction of the PVA component enhances the mechanical properties of the hydrogel.

[0141] (4) Analysis of the mechanical properties of double network hydrogels formed by adding different amounts of PVA

[0142] Test results such as Fig.10 shown. Fig.10 The results of the double network hydrogel prepared by adding different amounts of PVA solution showed that PVA:CEC:OHA=6:6:1 and PVA solution was 15wt%, with the best mechanical properties (elastic modulus of 164.47KPa). When the PVA concentration was 20wt%, the elastic modulus was 148.60KPa. The reason is that when the concentration of PVA solution increases, on the one hand, the viscosity of the solution increases, making it difficult for the molecular chain to move, making it difficult to cross-link with adjacent PVA molecular chains to form intermolecular hydrogen bonds, and the formation of microcrystalline areas is also hindered, resulting in the instability of the three-dimensional network of the hydrogel; on the other hand, high concentrations of PVA will produce more bubbles, thus affecting the mechanical properties.

[0143] Example 5. SEM test

[0144] SEM is a means of characterizing the surface morphology of materials, and uses different electronic signals formed by the interaction between the electron beam and the sample surface for microscopic imaging. Its working principle is that the high-energy electron beam interacts with the sample surface, obtains characteristic signals, and forms characteristic images through the imaging function of the instrument. The present invention uses a scanning electron microscope to observe the morphological structure of the hydrogel. The freeze-dried hydrogel sample is quenched in liquid nitrogen for 30 seconds and then brittle fractured. Then the brittle fracture section is sprayed with gold for 1 minute, and the microscopic pore structure of the hydrogel is observed under magnifications of 500 times and 1000 times. Samples 3, 4, 6, 12, and 13 in Tables 3 to 4 are sprayed with gold and then characterized in surface morphology under a scanning microscope.

[0145] SEM results are as follows Figure 11 to Figure 15 As shown. Fig.11 In the single network hydrogel without adding PVA solution, the pore structure is sparse and unevenly distributed. Figure 12 to Figure 14 In the figure, the pore structure of the double network hydrogel after adding the PVA solution is uniform and dense, showing a very obvious pore structure. When the number of cycles of freezing and thawing is 2, the pore structure is very uniform and dense. However, when the number of cycles of freezing and thawing increases to 3, the pore structure becomes larger and more irregular. The reason for this phenomenon may be that the cross-linking degree of PVA has been saturated, and continuing the cycle of freezing and thawing leads to overlapping of pore structure or accumulation of closed pores. For details, see Fig.15 .

[0146] The pore sizes of the samples of each ratio are shown in Fig.16 Among them, the pore size of the single network hydrogel with CEC:OHA=6:1 is 13.28±6.2μm, the pore size of the double network hydrogel prepared under the condition of 0 cycles with PVA:CEC:OHA=6:6:1 is 11.01±6.1μm, the pore size of the double network hydrogel prepared under the condition of 1 cycle with PVA:CEC:OHA=6:6:1 is 10.69±6.2μm, the pore size of the double network hydrogel prepared under the condition of 2 cycles with PVA:CEC:OHA=6:6:1 is 7.53±5.3μm, and the pore size of the double network hydrogel prepared under the condition of 3 cycles with PVA:CEC:OHA=6:6:1 is 8.23±4.8μm. From the pore size, it can be seen that the pore size of the single-network hydrogel is almost twice that of the double-network hydrogel prepared under PVA:CEC:OHA=6:6:1 and 2-cycle conditions. This proves that the addition of the PVA system to the hydrogel will make the three-dimensional structure of the hydrogel more stable.

[0147] Example 6. Self-healing and injectable performance experiments

[0148] This example further verifies the self-healing and injectable properties of the sample obtained in Example 1. The self-healing property of the single network hydrogel comes from the dynamic Schiff base formed by CEC and OHA, while the self-healing property of the double network hydrogel is the combined effect of the dynamic Schiff base and the dynamic borate ester bond, see Fig.17 The self-healing and injectable performance test methods and results are as follows:

[0149] (1) Methods

[0150] Single and double network hydrogels were prepared under the same conditions as samples No. 3 and No. 6 in Example 1 and stained with Rhodamine B. The hydrogels were cut into two halves and the two halves were seamlessly placed on the fracture surface without any external pressure at room temperature to allow self-healing, and their microscopic healing was observed under a microscope. The self-healing hydrogel was subjected to a pressure test under the same mechanical test conditions. The mechanical properties of the self-healing hydrogel were compared with those of the original hydrogel to determine whether the self-healing performance was good or not, and to calculate its self-healing rate.

[0151] The self-healing rate is calculated as follows:

[0152]

[0153] Among them, S 1 is the mechanical properties after self-healing, S 0 are the mechanical properties before self-healing.

[0154] The prepared hydrogel is injected into a syringe, and then the hydrogel in the syringe is squeezed to draw a fixed shape.

[0155] (2) Results

[0156] Sodium tetraborate is weakly alkaline when dissolved in water, and the borate ions react with the ortho-hydroxyl groups on PVA to form dynamic borate ester bonds, and the reaction is very rapid. When the hydrogel is broken and reconnected, the molecular chains in the hydrogel flow very quickly, and a large number of hydroxyl groups in PVA quickly combine with borate ions to reform borate ester bonds, achieving rapid self-healing. Therefore, the improvement in the self-healing performance of the hydrogel double network compared to the single network is due to the rapid formation of dynamic borate ester bonds.

[0157] Test results such as Figures 18 to 20 As shown. Among them, Fig.18 -A. Fig.18 -B is a diagram of the self-healing process of 6:1 single network hydrogel at the macro and micro levels. Fig.18 -C. Fig.18 -D is a diagram of the self-healing process of the 6:6:1 dual network at the macro and micro levels. Fig.18-A shows that the single network hydrogel cross-linked by Schiff base bonds still has obvious gaps during the whole healing process. The color of the whole hydrogel is fused at 1.5h, and there are still gaps at 12h under macroscopic observation. The effect is poor when it is stretched, and it is fragile and easy to break. Fig.18 -C It can be seen that the hydrogel formed by cross-linking of Schiff base bonds and dynamic borate bonds in this experiment has super strong self-healing properties. The gaps in the hydrogel have disappeared at 3s, the hydrogel has completely self-healed at 3min, and the entire interface has almost turned red at 1h. Fig.18 -D shows that after 2 hours, the other half of the originally transparent hydrogel has been dyed light pink, and after 12 hours, the entire hydrogel is red. At the same time, when the hydrogel that has been self-healed for 12 hours is stretched, no self-healing gaps can be seen at all and the color is uniform. It cannot be pulled apart by applying force with tweezers. The above results show that the dual-network hydrogel not only has greatly improved mechanical properties compared to the single-network, but also has better self-healing properties.

[0158] Fig.19 Figure 2 shows the stress-strain curves and elastic modulus diagrams of single and double network hydrogels before and after self-healing. Fig.19 -A. Fig.19 -B It can be found that when the mechanical properties were tested 12 hours after self-healing, the mechanical properties and elastic modulus of the hydrogel before and after single and double network self-healing were not much different, proving that the hydrogel prepared in this experiment has relatively good self-healing performance, with a single network self-healing rate of 96.91% and a double network self-healing rate of 98.40%.

[0159] Fig. 20 The word "china" is written with a syringe. Fig. 20 It can be seen that after the hydrogel is crushed by a mechanical instrument and injected into a syringe, the granular hydrogel injected from the syringe can be cross-linked within 30 seconds and form a fixed shape without obvious granular traces.

[0160] Example 7. Rebound and stretchability test

[0161] This example tests the rebound and stretchability of sample No. 6 in Example 1. The experimental method and results are as follows:

[0162] (1) Rebound performance test

[0163] The cylindrical hydrogel (hydrogel: diameter 10 mm, height 5 mm) was compressed to the maximum compression amount at a rate of 5 mm / min under a mechanical tester, and its rebound performance was observed after the compression mold was removed.

[0164] The results are as follows Fig.21As shown, the original length of the hydrogel is 5 mm. When it is compressed from 5 mm to the maximum fragmentation height of 1 mm, the hydrogel can recover to 5 mm in a short time, proving that the hydrogel prepared in this experiment can quickly restore its original shape and performance without being crushed, and has good resilience.

[0165] (2) Stretchability test

[0166] The prepared long strip hydrogel (stained with Rhodamine B) was placed horizontally under a ruler to measure its original length, and then the hydrogel was horizontally stretched to the maximum breaking point and its length was measured under a ruler.

[0167] The formula for calculating the stretch ratio is as follows:

[0168]

[0169] The results are as follows Fig. 22 As shown, the original length of the hydrogel was 4 mm, which was stretched to 7 mm using tweezers, with a stretching ratio of 75%.

[0170] Example 8. Swelling performance experiment

[0171] In order to detect the swelling rate of the hydrogel, the cylindrical freeze-dried hydrogel samples (samples 3, 4, 6, 12, and 13 in Tables 3 to 4) were immersed in 37°C PBS buffer (pH = 7.4), and 5 parallel samples were set up in each group. At the predetermined time, the swollen hydrogel was quickly weighed after removing the excess water on the surface with filter paper (5 min, 10 min, 15 min, 30 min, 1 h, 2 h, 3 h, 5 h).

[0172] The swelling ratio is calculated as follows:

[0173]

[0174] Where Ws is the wet weight of the swollen hydrogel at a given time, pH and temperature, and W d is the dry weight of the hydrogel.

[0175] The results are as follows Fig.23 As shown, the swelling curve of the hydrogel prepared by the present invention tends to be stable and reaches the maximum swelling degree at 5h, the swelling rate of the single network is as high as 2500%, and the swelling rate of the double network hydrogel is 1000%. Among them, the swelling performance of the single network hydrogel is better than that of the double network hydrogel. The reason for this phenomenon is that the internal cross-linking degree of the single network hydrogel is not high and the structure is loose; for the double network, the 3:6:1 / 2 cycle is relatively high, and the reason is that the amount of PVA solution added is small and the cross-linking degree is high; the hydrogel of the 6:6:1 / 0 cycle has no uniform three-dimensional structure inside because it is frozen-thawed, making it easy for PBS solution molecules to enter the network.

[0176] Example 9. Shape memory and ion conduction experiments

[0177] (1) Shape memory experiment

[0178] The prepared long strip hydrogel (stained with Rhodamine B) was soaked in a pH = 4 HCl aqueous solution. When the hydrogel was in a limp state, it was transferred to a pH = 11 NaOH aqueous solution to shape it. Finally, it was transferred to an HCl aqueous solution to observe its morphological changes and the time taken.

[0179] The results are as follows Fig.24 As shown, the hydrogel changes from a "U" shape to a "-" shape to an "O" shape, and then back to a "-". This result shows that the hydrogel can withstand at least 2 cycles of shape memory. The shape of the hydrogel frozen in a sodium hydroxide solution (pH = 11) can form a simple shape, and can quickly recover to its original straight strip shape in a hydrochloric acid solution (pH = 4) within 130 seconds. In a more complex three-dimensional spiral shape, it can quickly recover to its original straight strip shape in a hydrochloric acid solution (pH = 4) within 350 seconds.

[0180] The shape memory behavior of the hydrogel is the result of the formation and dissociation of the microcrystalline region of the chitosan molecular chain and the pH response of the dynamic borate ester bond. When the hydrogel is immersed in an alkaline solution, the microcrystalline region of the chitosan begins to deprotonate, and the shape can be fixed at will; when immersed in an acidic solution again, the amino groups on the chitosan are reprotonated, and the repulsive force between the molecules causes the microcrystalline region to be destroyed, resulting in the inability to maintain the manufactured shape. The dynamic borate ester bond can serve as a temporary cross-linking point for the hydrogel to maintain its shape. Once the hydrogel is endowed with shape memory behavior, it can be fixed in any temporary shape, extending its service life, and can be used in both acidic and neutral environments.

[0181] (2) Ionic conductivity experiment

[0182] The present invention uses a battery, a wire, and a light bulb to connect a simple circuit. Two electrodes are inserted into the hydrogel to observe whether the light turns on, and then the hydrogel is cut off and reconnected to observe whether the light turns on again. The resistivity of hydrogels with different proportions is tested by a four-probe method, and each hydrogel is tested twice, and the average value is calculated to calculate the ionic conductivity.

[0183] The formula for calculating ionic conductivity is as follows:

[0184]

[0185] The results are as follows Fig.25 and Fig.26 As shown, Fig.25In order to measure the statistical results of ionic conductivity of each ratio using the four-probe method, it can be seen that the single network has a lower resistivity and the highest conductivity due to the low cross-linking of the internal structure; for the double network, the hydrogel that has not undergone cyclic freezing-thawing has a higher conductivity than the hydrogel that has undergone cyclic freezing-thawing, and the reason is also the irregular internal three-dimensional structure and large pore size. Fig.26 This is a diagram of the ion conduction process, which shows the conductivity of the double network hydrogel. When the hydrogels come into contact, the dynamic cross-links between the interfaces will be reformed, the hydrogels will self-repair, and the conductive paths will be regenerated, allowing the lamp to glow again with basically unchanged brightness.

[0186] The reason why the double network hydrogel has ion conductivity is that the sodium tetraborate solution contains borate and sodium ions. The presence of ions enables the hydrogel to adapt well to the deep wound cavity, promote signal conduction between cells and external electrical stimulation, and also slow down the blood flow and prolong the coagulation time, which increases the oxygen content in the blood and is beneficial to the transportation, absorption and utilization of blood oxygen, thereby promoting wound healing.

[0187] Example 10. Drug release experiment

[0188] Doxycycline hydrochloride is a tetracycline antibiotic. Its mechanism of action is mainly to destroy bacterial protein synthesis without destroying bacterial cell walls. It has a bactericidal effect and is usually used to inhibit bacterial reproduction. It has a positive effect on wound healing. This drug release and antibacterial behavior experiment was conducted using doxycycline hydrochloride at a drug concentration of 0.05g / mL. The double-network drug carrier is a PVA solution, and the single-network drug carrier is a CEC solution. Doxycycline hydrochloride will show an obvious ultraviolet absorption peak at 215nm.

[0189] Draw a standard curve for doxycycline hydrochloride: weigh 0.015g of doxycycline hydrochloride and dissolve it in 3mL of PBS buffer. The initial solution concentration is 5mg / mL. Then measure the absorbance of 5mg / mL, 1mg / mL, 0.5mg / mL, 0.1mg / mL, 0.05mg / mL, 0.01mg / mL, and 0.005mg / mL in turn under a UV spectrophotometer. Draw a fitting line and R according to the relationship between absorbance and concentration. 2 . Test sample absorbance: Soak the drug-loaded hydrogels with different conditions (No. 3, 4, 6, 12, and 13 in Tables 3 to 4) in 2 mL of PBS buffer, take out 1 mL of PBS buffer at 1h, 3h, 6h, 10h, 15h, 20h, and 25h, and add 1 mL of PBS buffer at the same time, and then test its absorbance with a UV spectrophotometer. Draw a cumulative release rate curve: According to the corresponding relationship of the fitting straight line, find the concentration corresponding to each sample, and draw a cumulative release rate curve over time based on this concentration.

[0190] Results: The fitting straight line of doxycycline hydrochloride was C = 0.3965A + 0.2497 (R 2 =0.9891), the cumulative release curve of drug loading within 25h is as follows Fig. 27 As shown. It is well known that the cumulative release rate of drug-loaded hydrogel should not be too high or too low. If it is too high, the drug property will disappear quickly and the service life will not be extended; if it is too low, the hydrogel will not have a good antibacterial effect within a certain period of time. According to the doxycycline hydrochloride fitting straight line and Fig. 27 It can be seen that the hydrogels with different ratios only have sustained release, without sudden release or suspended release, and the release rate of the hydrogel prepared by the 6:1 single network is relatively high, the reason is that the internal structure of the single network hydrogel has a low degree of cross-linking and the drug loss is fast. For the double network, the cumulative release rate of the hydrogel prepared by the 6:6:1 (PVA 15wt%) double network / 0 cycles is higher than that of the 2 cycles, the reason is that the hydrogel that has not undergone cyclic freezing-thawing has no crystallization phenomenon inside, the cross-linking degree is low, and the intermolecular resistance of drug release is smaller. The cumulative release rate of the hydrogel prepared by the 6:6:1 double network / 2 cycles (PVA 20wt%) is the highest in the double network, the reason is that the higher the concentration of PVA, the more excessive the crystallization of the cross-linked network will be, resulting in closed pores and collapse of some networks, thereby accelerating the drug release. The hydrogels prepared by 3:6:1 double network / 2 cycles (PVA 15wt%) and 6:6:1 double network / 2 cycles (PVA 15wt%) have the characteristics of high degree of cross-linking, and there is a phenomenon of "blocked release" of drugs, so that the cumulative release rate within 25 hours is only 13.04% and 12.1%, achieving sustained drug release.

[0191] Example 11. Antibacterial behavior experiment

[0192] The antibacterial activity of the hydrogel was studied by in vitro antibacterial test. The preparation method of LB medium is as follows: add 5g of peptone, 2.5g of yeast powder, 5g of sodium chloride and 10g of agar to a sterilized volumetric flask, then add 500mL of deionized water and sterilize again. Preparation of LB agar plate: Pour LB medium at 50°C evenly into the culture dish, about 10mL of culture medium per culture dish, wait for it to solidify naturally, apply sealing glue, and place it upside down in a 4°C refrigerator for use. Evenly spread the fresh bacterial culture suspension of Escherichia coli on the agar plate. All samples (samples 3, 4, 6, 12, and 13 in Tables 3 to 4) were cut into circles, and the diameter of each sample was about 1 cm. Sterile water (blank control group), non-drug-loaded hydrogel, and drug-loaded hydrogel were sterilized under ultraviolet light for 30 min, gently placed on the inoculated agar plate, and incubated in a cell culture incubator at 37°C for 12 h. The antibacterial activity obtained obvious inhibition zones, and the antibacterial activity of the hydrogel was evaluated by comparing the diameters of the inhibition zones.

[0193] The test results are as follows Figure 28-29shown. Fig.28 The results of antibacterial behavior at different ratios are shown in the figure. It can be seen that the hydrogel without drug loading has no antibacterial behavior. The reason is that due to the protonation of chitosan amino groups, pure water-soluble chitosan generally has an antibacterial effect in acidic media, but the effect is not obvious in neutral media.

[0194] Fig.29 The following is a statistical chart of the diameter of the hydrogel antibacterial zone under various preparation conditions. It can be seen that the single network hydrogel has the most obvious antibacterial effect. The reason is that its internal structure has a low degree of cross-linking and a large molecular gap, and doxycycline hydrochloride molecules can easily flow out from the gap. Compared with other ratios of double network hydrogels, the 6:6:1 double network / 0 cycle has the largest antibacterial zone. This is because the hydrogel that has not undergone cyclic freezing-thawing has a low degree of internal cross-linking, less crystallization, and a large internal pore diameter. The 6:6:1 double network / 2 cycles (PVA 20wt%) also has a large antibacterial zone. This phenomenon occurs because the PVA concentration is too high, resulting in the destruction of the original three-dimensional pore structure after two cycles of freezing-thawing. On the contrary, the antibacterial effects of 3:6:1 double network / 2 cycles and 6:6:1 double network / 2 cycles (PVA 15wt%) are the least obvious, because the internal cross-linking degree is high and the drug loss is relatively slow. For comparison, other literature can be consulted. Ag-loaded + The antibacterial zone of the hydrogel was about 1.7 cm ± 0.20 cm, and the Zn + The antibacterial zone of the hydrogel loaded with amoxicillin is about 1.5±0.12cm, and the antibacterial zone of the hydrogel loaded with amoxicillin is about 1.9±0.22cm. Therefore, the drug-loaded hydrogel prepared in this experiment has relatively good antibacterial properties. The results of the antibacterial behavior experiment and the drug release experiment are basically consistent.

[0195] Based on the test results of Examples 1 to 11 above, the following conclusions can be drawn:

[0196] (1) Based on the results of mechanical property tests, the optimal ratio of single network self-healing hydrogel is CEC:OHA=6:1, with an elastic modulus of 34.50KPa, and the optimal ratio of double network is PVA:CEC:OHA=6:6:1 (PVA 15wt%), with an elastic modulus of 164.47KPa, PVA:CEC:OHA=6:6:1 (PVA 20wt%), with an elastic modulus of 148.60KPa. The mechanical properties of double network hydrogel are 6 times higher than those of single network hydrogel. Chemical crosslinking by immersion in sodium tetraborate is better than adding sodium tetraborate. Cyclic freezing-thawing twice has the best effect on double network, indicating that the addition of PVA solution has successfully enhanced its mechanical properties.

[0197] (2) According to the results of the self-healing experiment, the self-healing rate of the single network is 96.91%, and the self-healing rate of the double network is as high as 98.40%. In addition, the double network hydrogel heals rapidly within only 3 seconds, no gaps appear within 5 hours, and it can be stretched arbitrarily without breaking within 12 hours. This proves that the self-healing effect of the prepared double network hydrogel is improved while ensuring excellent mechanical properties.

[0198] (3) The ionic bonds formed by the addition of sodium tetraborate crosslinker give the hydrogel shape memory and ionic conductivity behavior. At the same time, the ions present in the hydrogel can further promote wound healing and coagulation.

[0199] (4) Through drug release and antibacterial behavior, it was concluded that the double network had a good antibacterial effect when PVA:CEC:OHA=6:6:1 (PVA 20wt%), and the drug release cycle was long and slow, which provided a guarantee for the recycling of wound dressings.

[0200] Based on the mechanical properties of each proportion of the double network as well as the results of antibacterial and drug release, it can be concluded that when the CEC concentration is 3wt%, the OHA concentration is 10wt%, the PVA concentration is 20wt%, the volume ratio of PVA / CEC / OHA is 6:6:1, the freeze-thaw cycle is repeated twice, and then the double network hydrogel is soaked in sodium tetraborate for 30 minutes, the performance is better, which provides a basis for the preparation of new self-healing wound dressings.

Claims

1. A composition for preparing a high-strength double-network self-healing hydrogel, characterized in that: The composition comprises composition A for constructing a first hydrogel network system and composition B for constructing a second hydrogel network system; composition A comprises modified chitosan and modified hyaluronic acid, and composition B comprises polyvinyl alcohol and sodium tetraborate; the volume ratio of the polyvinyl alcohol, modified chitosan and modified hyaluronic acid is 5-7:5-7:1; the concentration of the modified chitosan is 2wt%-4wt%, the concentration of the aldehyde-modified hyaluronic acid is 8wt%-12wt%, and the concentration of the polyvinyl alcohol is 18wt%-22wt%.

2. The composition according to claim 1, characterized in that The amino groups on the modified chitosan are coupled with acrylic acid; and the modified hyaluronic acid is hyaluronic acid modified with aldehyde groups.

3. The composition according to claim 1, characterized in that The amino group of the modified chitosan and the aldehyde group of the modified hyaluronic acid form a dynamic Schiff base bond to form a first network; the sodium tetraborate and the polyvinyl alcohol form a dynamic borate ester bond to form a second network.

4. The composition according to claim 1, characterized in that The concentration of the modified chitosan is 3wt%, the concentration of the aldehyde-modified hyaluronic acid is 10wt%, the concentration of the polyvinyl alcohol is 20wt%, and the concentration of the sodium tetraborate is 1wt%; The volume ratio of the polyvinyl alcohol, modified chitosan and aldehyde-modified hyaluronic acid is 6:6:

1.

5. The method for preparing the high-strength double-network self-healing hydrogel according to any one of claims 1 to 4, characterized in that: The steps include: (1) dissolving acrylic acid and adding chitosan, coupling the amino groups on chitosan with acrylic acid through Michael reaction to obtain modified chitosan; (2) mixing hyaluronic acid with sodium periodate to prepare aldehyde-modified hyaluronic acid through an oxidation reaction; (3) mixing the modified chitosan obtained in step (1), the aldehyde-modified hyaluronic acid obtained in step (2) and polyvinyl alcohol, and rapidly stirring to form a gel; and soaking in sodium tetraborate after cyclic freezing-thawing to obtain the high-strength double-network self-healing hydrogel.

6. The preparation method according to claim 5, characterized in that: In step (3), the number of cycles of freezing and thawing is 2 times, the single freezing time is 2.5h to 3.5h, and the thawing time is 1.5h to 2.5h.

7. The preparation method according to claim 5, characterized in that: In step (3), the sodium tetraborate soaking time is 25 min to 60 min.

8. A high-strength double-network self-healing hydrogel prepared by the method described in any one of claims 5 to 7.

9. A preparation composition having an antibacterial effect, characterized in that: The preparation composition comprises the composition according to any one of claims 1 to 4 and an antibacterial drug, wherein the antibacterial drug comprises doxycycline hydrochloride, and the carrier of the antibacterial drug is polyvinyl alcohol.

10. Use of the composition according to any one of claims 1 to 4, the high-strength double-network self-healing hydrogel according to claim 8 and / or the preparation composition according to claim 9 in the preparation of a high-strength self-healing wound dressing.

Citation Information

Patent Citations

  • Antibacterial self-healing composite dual-network hydrogel as well as preparation method and application thereof

    CN116751432A

Cited By

  • High-strength degradable self-healing hydrogel and preparation method thereof

    CN120718300A